2019
DOI: 10.1039/c9nr00846b
|View full text |Cite
|
Sign up to set email alerts
|

Few layer graphene does not affect the function and the autophagic activity of primary lymphocytes

Abstract: Primary lymphocytes ensure their efficient function and maintenance through different mechanisms including autophagy. Few layer graphene does not affect either the viability and activation or the autophagic activity of B and T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…To investigate how FLG influences autophagy in primary macrophages, BMDMs were incubated with low (10 µg/mL) and high (100 µg/mL) doses of graphene for 24 h. A representative immunoblot (Figure 2A) of cell lysates of untreated, low-and high-dose FLG-treated and LPS-treated conditions shows the expression of LC3-I and -II with or without lysosomal protease inhibitors (E64D and pepstatin A). The expression of LC3 proteins in low-and high-dose FLG-treated cells is similar to basal level as observed in untreated cells and LPS-treated cells [22] and was observed to be slightly higher in the presence of protease inhibitors, indicating the inhibition of the degradation of autophagosomes. The visualization of LC3 bands is, however, not enough to attest to the influence of FLG on autophagic activity induction in macrophages, hence the densitometric ratio was calculated between membrane-bound LC3-II protein and β-actin (internal loading reference).…”
Section: Autophagic Activitysupporting
confidence: 75%
See 2 more Smart Citations
“…To investigate how FLG influences autophagy in primary macrophages, BMDMs were incubated with low (10 µg/mL) and high (100 µg/mL) doses of graphene for 24 h. A representative immunoblot (Figure 2A) of cell lysates of untreated, low-and high-dose FLG-treated and LPS-treated conditions shows the expression of LC3-I and -II with or without lysosomal protease inhibitors (E64D and pepstatin A). The expression of LC3 proteins in low-and high-dose FLG-treated cells is similar to basal level as observed in untreated cells and LPS-treated cells [22] and was observed to be slightly higher in the presence of protease inhibitors, indicating the inhibition of the degradation of autophagosomes. The visualization of LC3 bands is, however, not enough to attest to the influence of FLG on autophagic activity induction in macrophages, hence the densitometric ratio was calculated between membrane-bound LC3-II protein and β-actin (internal loading reference).…”
Section: Autophagic Activitysupporting
confidence: 75%
“…Recently, it has been reported that FLG can induce oxidative stress and endoplasmic-mediated autophagy in RAW264.7 macrophages [21]. In primary T and B cells, in contrast, our group has found that FLG does not impact viability and activation, nor autophagic activity [22].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recently, a comprehensive study has been published demonstrating how FLG does not affect the function and the autophagic activity of primary lymphocytes. [30] The results showed that FLG neither impacts the viability and activation of T and B cells nor their autophagic activity. Before studying the effects of G-Rib in an animal model, we wanted to evaluate the cytotoxic effects in two different cell lines.…”
Section: Exfoliated Graphene Synthesis and Characterizationmentioning
confidence: 93%
“…While in some studies cytotoxicity was observed [95][96][97][98][99], GNM-induced autophagy in healthy, non-transformed primary cells was usually not associated with significant cell death [100][101][102][103][104][105][106]. The certain types of normal cells such as mouse lymphocytes and monkey fibroblasts were apparently resistant to both autophagy-modulating and cytotoxic action of GNM [107,108]. Interestingly, in a direct comparison under the same experimental conditions, GO/chloroquine conjugate at moderate concentration (25 µg/mL) induced autophagy-dependent necroptosis in lung carcinoma cells, but not in their non-cancerous counterparts [43].…”
Section: Selectivity Of Gnm-mediated Autophagy Modulation In Anticancer Therapymentioning
confidence: 99%